Formulasi Sediaan Shampo Kombinasi Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius Roxb) dan Daun Seledri (Apium graveolens L.) sebagai Antiketombe terhadap Jamur Candida albicans - Danayasa, I Kadek; Yudianti Mendra, Ni Nyoman; Sunadi Putra, I Made Agus (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Dandruff is a scalp condition characterized by an anomaly, often caused by the fungus of Candida albicans. The development of safe and effective anti-dandruff shampoo is imperative. Notably, traditional medicine employs pandan wangi and celery leaves, rich in polyphenols, flavonoids, saponins, tannins and alkaloids as potential anti-dandruff agents. The aims of this study was to formulate and evaluate the antifungal activity of a combination shampoo containing extracts form pandan wangi and celery leaves. Antifungal testing was carried out using the diffusion method using paper discs. Three formulations were prepared FI (without extract), FII (10% pandan leaf extract, 20% celery leaf), FIII (20% pandan leaf extract, 10% celery leaf). Antifungal test was evaluated using the paper disc diffusion method, with 2% ketoconazole shampoo as the positive control. Physical quality test demonstrated favorable attributes for pandan wangi and celery leaf extract shampoo, with FII and FIII exhibiting dark green colors whit distinct odors, while FI remained colorless and odorless. Furthermore, all formulations were in semi-solid dosage forms and met pH requirement for scalps (pH 6,) and produced satisfactory foam yields (6,8-8,9 cm). The antifungal activity test revealed FI as the negative control with a 7 mm and 2% ketoconazole shampoo with a 24 mm inhibition zone, while FII and FIII showed no inhibition zone. The combination of pandan wangi and celery leaf extract in shampoo preparation showed no synergic activity to inhibit the growth of Candida albicans fungus. Further investigations and clinical trials are warranted to validate its effectiveness and safety for practical application.